2022
DOI: 10.7150/ijbs.70708
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline binds and inhibits LYN activity to prevent STAT3-meditated metastasis of colorectal cancer

Abstract: Colorectal cancer (CRC) is one of the most common malignancies worldwide. Metastasis is a major cause of CRC recurrence and mortality. Several antibiotic drugs have been reported to exert potential anticancer activities, however, whether and how the tetracycline antibiotic minocycline exhibit tumor suppressive effect on CRC remains unknown. Here, we found that minocycline markedly inhibits the epithelial-mesenchymal transition (EMT) process and metastasis of CRC cells both in vitro and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Previous reports on higher incidence of PTC in black thyroid can be a comprehensible finding, since the recognition of black thyroid predominantly occurs during surgery. Spared pigmentation in malignant tumors compared to surrounding tissue and the unproven carcinogenic activity of minocycline still raise questions on their relationships (9,21). Thus, proper treatment strategy has not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports on higher incidence of PTC in black thyroid can be a comprehensible finding, since the recognition of black thyroid predominantly occurs during surgery. Spared pigmentation in malignant tumors compared to surrounding tissue and the unproven carcinogenic activity of minocycline still raise questions on their relationships (9,21). Thus, proper treatment strategy has not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…; Advanced treatments that are still in the research and development stage, such as gene therapy, cell therapy, targeted immunotherapy, etc. However, each therapy has its drawbacks, such as tumor recurrence, lack of speci city of targets, and resistance to anticancer drugs [20][21][22] . Therefore, it is very necessary to improve and explore the treatment of Colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Minocycline is a tetracycline derivative that inhibits pro-inflammatory cytokines and metalloproteinases that are associated with tumor invasion and metastasis development, and, for this reason, this drug is in clinical trials to be repurposed for PC treatment, in which it has been found that minocycline inhibits LYN kinase and STAT3, suppresses EMT and consequently blocks metastases [ 2 , 34 ]. On the other hand, the chemical modification of tetracyclines (CMT-3) by activating caspase-3 and caspase-9 and by inhibiting metalloproteinases induces apoptosis in PC cells [ 2 , 5 ].…”
Section: Pharmacotherapeutic Groups With Potential Efficacy In Pc Tre...mentioning
confidence: 99%